Feed and fodder production in different agro-climatic zones and its utilization for livestock of Odisha - Swain, Braja; Teufel, Nils; Lukuyu, Ben A. (International Livestock Research Institute, 2023)
These data contain one round cross section, details about the 2268 households having livestock covering 10 Agro-climatic zones of Odisha. This database includes information on livestock holding, landholding, cropping pattern, feed availability, access to different type of feed, contribution of different feed in total feed intake of dairy animals. In addition, this database also includes the knowledge level among farmers and training received. This data will help other know feed access by farmers in eastern India and the knowledge level.